A young girl with recurrent Fallopian Tube Carcinoma (FTC): an interesting case report - May, Zaw Soe; Elaine Chung; Suguna Subramaniam; Yeap, Boon Tat; Abdel Mohsen Mohamed Ahmed Abdel Hafez; Tin Tin Thein; Ehab Helmy Abdel Malek Fahmy (Penerbit UMS, 2024)
Primary fallopian tube carcinoma (FTC) is a rare disease which frequently occurs among post-menopausal women. It is often grouped under the epithelial ovarian cancer umbrella. The treatment of choice is surgery and chemotherapy. Our patient was a young teenage girl with recurrent FTC who responded well to surgery and chemotherapy. We discuss on the epidemiology, risk factors, principles of management and prognosis of FTC.